The Relationship Of Interest In Participating Extracurricularies With The Discipline Of Scout Members At SMP Negeri 3 Padang - Hasanah, Rizatul; Natsir, MHD (Universitas Negeri Padang, 2023)
This research was motivated by the low discipline of scout members at SMP Negeri 3 Padang, which was thought to be due to interest. This research aims to see a picture of interest in taking part in extracurriculars, see a picture of the discipline of scout members, and see the relationship between interest in taking part in extracurriculars and the discipline of scout members at SMP Negeri 3 Padang. This type of research is quantitative correlational. The population of this study was 24 active scout members from SMP Negeri 3 Padang. The sampling technique in this research was carried out using the target sampling method, so that the total sample taken by the researchers was 19 people. The data collection technique in this research is a questionnaire. Meanwhile, the data analysis method in this research is the Spearman Rank correlation method. The results of this research indicate that members' interest in participating in scout extracurriculars and the discipline of scout members is low and there is a relationship between interest in participating in extracurricular activities and the discipline of scout members at SMP Negeri 3 Padang. It is recommended that coaches be more creative in developing programs for scout extracurricular activities so that members' interest and discipline increases. Suggestions for future researchers are to be able to identify other variables besides interest in participating in extracurricular activities that can have an influence on the discipline of scout members. Keywords: Scouting Interests, Disciplines, Extracurriculars.